Stakeholder insights for effective higher education management - Andaleeb, Syed Saad (© 2008 published jointly by BAFED and BU-IED, 2016)
This is an Open Access Article. It is a half-yearly journal published jointly by BAFED and BU-IED with financial assistance from UNESCO. The Journal's Retrieved from http://www.bafed.net/earchive.php